Pengembangan Modul Geometri Berbasis Etnomatematika Tari Ranup Lampuan Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SD - Desy Ravita; Bansu Irianto Ansari; Musdiani Musdiani (Jurnal Ragam Pengabdian, 2026)
This study is motivated by the low level of students’ mathematical problem-solving skills due to less contextual geometry instruction. It aims to develop a geometry learning module based on an ethnomathematics approach using the context of the Ranup Lampuan dance to improve fourth-grade students’ problem-solving abilities at SDN 01 Percontohan Meulaboh. The study employed a Research and Development (R&D) design with a mixed-methods approach. The participants consisted of 48 students, divided into an experimental group (24 students) and a control group (24 students). Data were collected through expert validation, tests, observations, questionnaires, and interviews, and analyzed using descriptive percentage analysis, N-Gain, and paired sample t-test. The results show that the developed module is valid, with ratings ranging from good to very good in terms of content, media, language, and cultural aspects, and is practical for classroom use. The module also increases students’ learning interest and facilitates understanding of geometric concepts through connections with local culture. Quantitatively, the average pretest score improved from 60.2 to 79.6 in the posttest, with an N-Gain value of 0.50 (moderate category). The paired sample t-test indicates a significant difference (p < 0.05). Therefore, the module is effective in improving students’ mathematical problem-solving skills.